2020
DOI: 10.1007/s11368-020-02801-1
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of polyaromatic hydrocarbon accumulation in rural gardens using lettuce plants

Abstract: Purpose Air pollution in settlements is one of the most important factors affecting human health. While urban gardening and the consumption of home-grown vegetables have become more and more popular, several studies establish the risk of consuming vegetables exposed to toxic air pollutants, especially polyaromatic hydrocarbons (PAHs). However, these studies mostly concern the risk in larger cities or in industrial areas while much less information is available in rural environments. Methods In our study, sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The prevalence of PAHs in the soil is mostly of anthropogenic origin (Zhou et al, 2005) due to the increasing use of energy from the combustion of fossil fuels, oil and internal combustion engines (Lui et al, 2017; Tiwari et al, 2011). Atmospheric PAHs accumulate easily in the soil due to their sorption capacity (Eom et al, 2007; Kováts et al, 2021) and arrive at the land surface through both wet and dry deposition (Choi et al, 2009; Ding et al, 2007). Organic pollutants are stored, captured and delivered to the litter in forest soils by tree crowns (Matzner, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of PAHs in the soil is mostly of anthropogenic origin (Zhou et al, 2005) due to the increasing use of energy from the combustion of fossil fuels, oil and internal combustion engines (Lui et al, 2017; Tiwari et al, 2011). Atmospheric PAHs accumulate easily in the soil due to their sorption capacity (Eom et al, 2007; Kováts et al, 2021) and arrive at the land surface through both wet and dry deposition (Choi et al, 2009; Ding et al, 2007). Organic pollutants are stored, captured and delivered to the litter in forest soils by tree crowns (Matzner, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to PTEs, polycyclic aromatic hydrocarbons (PAHs) are also widespread pollutants in soil, water, air, and plants [ 13 , 14 , 15 ]. They primarily result from the incomplete combustion or pyrolysis of organic materials, through incineration or industrial activities [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ]. Various studies have been conducted in these areas to assess soil and vegetable contamination [ 10 , 11 ]. Daimari et al (2020) assessed trace metal air pollutants in urban, peri-urban, and rural areas on the Brahmaputra Valley plain and found that metals related to automobiles were accumulated in greater volume in samples from peri-urban locations [ 12 ].…”
Section: Introductionmentioning
confidence: 99%